Proxy electrochemical process for Acid humic - Kashi, G.; Khoshab, F. (Ciência e Natura, 2015)
Humic substances are produced by the microbial degradation of dead plant matter. The goal of this research is to investigate of humic acid (HA) from urban drinking water by batch proxy electrochemical reactor(PER)with using zinc-copper electrode(distance 2 cm) and hydrogen peroxide. The variables include pH(4-10), concentration of HA(5-15 mg/L), reaction time(7.5-22.5 min), concentration of hydrogen peroxide(40-120 mg/L), and current density(3-9 mA/cm2). In electrochemical reactor, the removal percentage for HA concentration(5 mg/L) in current density 9 mA/cm2 and electrolysis time 15 min in pHs 4, 7, and 10 are obtained 61%, 56%, and 51%, respectively. In electrochemical reactor, the removal percentage for HA concentration (15 mg/L) in current density 9 mA/cm2 and electrolysis time 15min in pHs 4, 7, and 10 are obtained 41%, 36%, and 31%, respectively. In PER, the removal percentage for HA concentration (5 mg/L), in optimum conditions, in hydrogen peroxide concentration 120 mg/L, current density 9 mA/cm2, optimum pH 4, electrolysis time 15 min in HA concentrations 5, 10, and 15 are obtained 100%, 93%, and 83%, respectively. The findings indicate that HA removal efficiency is increased with increasing current density, electrolysis time, and decreasing HA concentration. PER has appropriate efficiency for the HA removal from water.